A review on development and application of plant-based bioflocculants and grafted bioflocculants - Lee, Chai Siah; Chong, Mei Fong; Robinson, John P.; Binner, Eleanor (American Chemical Society, 2014)
Flocculation is extensively employed for clarification through sedimentation. Application of eco-friendly plant-based bioflocculants in wastewater treatment has attracted significant attention lately with high removal capability in terms of solids, turbidity, color, and dye. However, moderate flocculating property and short shelf life restrict their development. To enhance the flocculating ability, natural polysaccharides derived from plants are chemically modified by inclusion of synthetic, nonbiodegradable monomers (e.g., acrylamide) onto their backbone to produce grafted bioflocculants. This review is aimed to provide an overview of the development and flocculating efficiencies of plant-based bioflocculants and grafted bioflocculants for the first time. Furthermore, the processing methods, flocculation mechanism, and the current challenges are discussed. All the reported studies about plant-derived bioflocculants are conducted under lab-scale conditions in wastewater treatment. Hence, the possibility to apply natural bioflocculants in food and beverage, mineral, paper and pulp, and oleo-chemical and biodiesel industries is discussed and evaluated.